The effectiveness of a group self‐management education course for adults with poorly controlled epilepsy, SMILE (UK): A randomized controlled trial. (16th April 2018) - Ridsdale, Leone; Wojewodka, Gabriella; Robinson, Emily J.; Noble, Adam J.; Morgan, Myfanwy; Taylor, Stephanie J. C.; McCrone, Paul; Richardson, Mark P.; Baker, Gus; Landau, Sabine; Goldstein, Laura H.
Summary: Objective: Epilepsy is one of the most common neurological conditions affecting about 1% of adults. Up to 40% of people with epilepsy (PWE) report recurring seizures while on medication. And optimal functioning requires good self‐management. Our objective was to evaluate a group self‐management education courses for people with epilepsy and drug‐resistant seizures by means of a multicenter, pragmatic, parallel group, randomized controlled trial. Methods: We recruited adults with epilepsy, having ≥2 seizures in the prior 12 months, from specialist clinics. Consenting participants were randomized 1:1 to a group course or treatment as usual. The primary outcome measure was quality of life 12 months after randomization using Quality of Life 31‐P (QOLIE‐31‐P). Secondary outcome measures were seizure frequency and recency, psychological distress, impact and stigma of epilepsy, self‐mastery, medication adherence, and adverse effects. Analysis of outcomes followed the intention‐to‐treat principle using mixed‐effects regression models. Results: We enrolled 404 participants (intervention: n = 205, control: n = 199) with 331 (82%) completing 12‐month follow‐up (intervention: n = 163, control: n = 168). Mean age was 41.7 years, ranging from 16 to 85, 54% were female and 75% were white. From the intervention arm, 73.7% attended all or some of the course. At 12‐month follow‐up, there were no statistically significant differences between trial arms in QOLIE‐31‐P (intervention mean: 67.4, standard deviation [SD]: 13.5; control mean: 69.5, SD 14.8) or in secondary outcome measures. Significance: This is the first pragmatic trial of group education for people with poorly controlled epilepsy. Recruitment, course attendance, and follow‐up rates were higher than expected. The results show that the primary outcome and quality of life did not differ between the trial arms after 12 months. We found a high prevalence of felt‐stigma and psychological distress in this group of people with drug‐resistant seizures. To address this, social and psychological interventions require evaluation, and may be necessary before or alongside self‐management‐education courses.